Virus-Heat Shock Protein Interaction and a Novel Axis for Innate Antiviral Immunity - Michael Oglesbee; Mi Young Kim (Cells, 2012)
Virus infections induce heat shock proteins that in turn enhance virus gene expression, a phenomenon that is particularly well characterized for the major inducible 70 kDa heat shock protein (hsp70). However, hsp70 is also readily induced by fever, a phylogenetically conserved response to microbial infections, and when released from cells, hsp70 can stimulate innate immune responses through toll like receptors 2 and 4 (TLR2 and 4). This review examines how the virus-hsp70 relationship can lead to host protective innate antiviral immunity, and the importance of hsp70 dependent stimulation of virus gene expression in this host response. Beginning with the well-characterized measles virus-hsp70 relationship and the mouse model of neuronal infection in brain, we examine data indicating that the innate immune response is not driven by intracellular sensors of pathogen associated molecular patterns, but rather by extracellular ligands signaling through TLR2 and 4. Specifically, we address the relationship between virus gene expression, extracellular release of hsp70 (as a damage associated molecular pattern), and hsp70-mediated induction of antigen presentation and type 1 interferons in uninfected macrophages as a novel axis of antiviral immunity. New data are discussed that examines the more broad relevance of this protective mechanism using vesicular stomatitis virus, and a review of the literature is presented that supports the probable relevance to both RNA and DNA viruses and for infections both within and outside of the central nervous system.